World class training [electronic resource] : providing training excellence - Thorne, Kaye (Kogan page, 2000)
A practical guide to delivering the best training in the world! Packed with examples of best practice and case studies from a wide variety of organizations such as Disney, Volvo, and Reckitt & Colman, World Class Training shows not only the best in action but demonstrates how both individual trainers and training departments can benchmark their performance against global leaders. Written in an easily accessible style, individual chapters focus on the role of the trainer, feedback, rewards, and values, attitude, and aptitude among other topics.